Methylation of human papillomavirus type 16 CpG sites at E2-binding site 1 (E2BS1), E2BS2, and the Sp1-binding site in cervical cancer samples as determined by high-resolution melting analysis-PCR (2013)
High-risk (HR) human papillomavirus (HPV)-associated carcinogenesis is driven mainly by the overexpression of E7 and E6 oncoproteins following viral DNA integration and the concomitant loss of the E2 open reading frame (ORF). However, the integration of HR-HPV DNA is not systematically observed in cervical cancers. The E2 protein acts as a transcription factor that governs viral oncogene expression. The methylation of CpGs in the E2-binding sites (E2BSs) in the viral long control region abrogates E2 binding, thus impairing the E2-mediated regulation of E7/E6 transcription. Here, high-resolution melting (HRM)–PCR was developed to quantitatively analyze the methylation statuses of E2BS1, E2BS2, and the specificity protein 1 (Sp1)-binding site in 119 HPV16-positive cervical smears. This is a rapid assay that is suitable for the analysis of cervical samples. The proportion of cancer samples with methylated E2BS1, E2BS2, and Sp1-binding site CpGs was 47%, whereas the vast majority of samples diagnosed as being within normal limits, low-grade squamous intraepithelial lesions (LSIL), or high-grade squamous intraepithelial lesions (HSIL) harbored unmethylated CpGs. Methylation levels varied widely, since some cancer samples harbored up to 60% of methylated HPV16 genomes. A pyrosequencing approach was used as a confirmation test and highlighted that quantitative measurement of methylation can be achieved by HRM-PCR. Its prognostic value deserves to be investigated alone or in association with other biomarkers. The reliability of this single-tube assay offers great opportunities for the investigation of HPV16 methylation in other HPV-related cancers, such as head and neck cancers, which are a major public health burden.